Causes and effects of water pollution in the Soniwein Community, Central Monrovia, Liberia (March to May 2017) - CHEA, Sampson K. P.; Andrew P., DEAN (International Journal of Basic and Applied Sciences, 2018)
Water pollution can be defined in many ways. Usually, it means one or more substances have built up in water to such an extent that they cause problems for animals or people. The objectives of this study were to determine the causes and effects of Water pollution in Soniwein Community and to determine whether the cases of water borne diseases can be attributed to unsafe and contaminated water in Soniwein Community as well as to come up with interventional strategies by which water pollution can be mitigated in the Soniwein Community. This research employed the cross sectional survey design. Field interviews were done by close-ended questionnaires, including health workers at Soniwein Community Clinic. Water samples were randomly collected and microbiological and chemical tests were conducted at the National Standards Lab to determined contamination by microbes and physical quality of the water respectively Samples were randomly collected from the Soniwein community and tested The microbiological test reveals a rejection in total viable count for Well 1, [2], [3] & [4], N/A in Yeasts & Mold, for Well 1, 2, 3, 4, detection of E. Coli in Well 1, 2, 3 & 4. The results of the chemical test reveals the iron content of Well [1-3] to be in acceptable range while that of well 4 was out of acceptable range; the chloride content of Well [1-4] were all in acceptable range; the pH values for Well 1, 2, 3 & 4 were all in normal rang; Well 1, 2, & 3 were all in acceptable turbidity range while that of well 4 showed a deviant. Water pollution in the Soniwein Community is caused by several factors such poor sanitation, improper disposal of domestic wastes and the effects lead to water- borne diseases such as Typhoid, Diarrhea and dysentery, and infants between the ages of 0-2 years are mostly affected.
Keywords: Microbiological; Chemical; Pollution; Contamination; and Water-Borne